THE EXISTENCE AND EFFECTIVENESS OF THE LAW ON THE APPLICABILITY OF THE CONSTITUTIONAL RIGHTS OF CITIZENS-NATURALIZATION IN ELECTIONS IN INDONESIA - Rifandhana, Raditya Feda; Budiono, Indro; Ningtias, Ayu Dian; Nurita, Riski Febria; Wahyono, Bambang Angkoso (Universitas Islam Lamongan, 2022)
AbstractIndonesia is a country based on the Constitution of the Unitary State of the Republic ofIndonesia of 1945, so that the basis of the country, has a basis on which it regulateshuman rights, human rights are not only the rights of Indonesian citizens, but the rightsof foreign citizens through naturalization, both citizen statuses have the same rights inelections, and in this writing using juridical research, So that the research is based onlaws and regulations, as well as a research approach with legal theory.